Implementation of Electronic Limitation Right (HT-el) by Debtor According to the Regulation of the Minister of Agrarian Affairs and Spatial Plan or Head of National Land Agency Number 5 Year 2020 Concerning Liability Service Integrated by Electronic - MM. Thanisa Dita Murbarani; I Gusti Ayu Ketut Rachmi Handayani; Yudho Taruno Muryanto (IJRAEL: International Journal of Religion Education and Law, 2022)
Mortgage Rights are Guarantee Rights that can be imposed on land rights. Mortgage rights are used for binding collateral in the form of land with using the deed made by the Land Deed Making Official. Mortgage right Electronics, also known as HT- el , is the first electronic service that issued for interest and give convenience Public in meet the needs by applying for a loan from a financial institution namely banking. Roya is the deletion of mortgage rights in the book of land rights and the certificate. scribble Right Dependent which has end is something must. Problems arise when the implementation of the write-off of Mortgage The electronics that are done are not appropriate and the validity of the deletion of the Mortgage Electronic based on PMATR/KBPN No 5 years 2020